Spiritual Development as a Factor of Professional and Personal Qualities of Modern Students - Kuatova, Zh.Zh.; Buletova, L.A.; Makhmutova, K. I.; Suleimenova, S.N.; Nuridinova, G. A.; Suleimenova, A. A. (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
This article deals with the formation of spiritual development of students, caused by three main circumstances: First, the need to study the changes taking place in society and changes in the mechanism of formation of spiritual culture of students. The hierarchy of values and spiritual activity of new generations of students differ significantly from previous generations' value-normative system. Secondly, students' innovative role in youth culture and a special place of higher education as a factor in the formation of students' spiritual culture. Third, considering students' specific qualities and characteristics as a special social group, the study of youth spiritual culture can determine the parameters of society's spiritual development prospects. In the works of the researchers mentioned above, in particular, the social aspects of cultural self-identification of young people were touched upon. The influence of deformations of the value-normative system on the strengthening of the processes of individualization of consciousness of young people taking place against the background of the destruction of rigid traditional forms of social control and the absence of new moral boundaries was studied. In connection with the social and educational environment, the issues of adaptation of young people were considered. Applied research in the higher education system reflects the urgent problems of universities. It contributes to the clarification of hypotheses and building theories of the middle level, including issues of institutional impact institutions of higher education on the formation of students' spiritual development, especially in terms of its professional component. The analysis of requests, expectations, and preferences of young generations in the field of culture makes it possible to form a holistic view of the development of leisure behavioral stereotypes